2013
DOI: 10.1155/2013/182694
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiamine Pyrophosphate in Prevention of Cisplatin Ototoxicity in an Animal Model

Abstract: Objective. The aim of this study was to evaluate the effectiveness of thiamine pyrophosphate against cisplatin-induced ototoxicity in guinea pigs. Materials and Methods. Healthy guinea pigs (n = 18) were randomly divided into three groups. Group 1 (n = 6) received an intraperitoneal injection of saline solution and cisplatin for 7 days, group 2 (n = 6) received an intraperitoneal injection of thiamine pyrophosphate and cisplatin for 7 days, and group 3 (n = 6) received only intraperitoneal injection of saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…On the other hand, SOD1 gene has been shown to interact with thiamine biosynthetic regulatory gene THI2 (Zheng et al ., ), showing that the network between thiamine, TDP and defence systems are probably much more complicated than previously presumed. An interesting example of those interactions has been also provided by two different groups, who reported that an oral administration of TDP but not thiamine yielded significant protection against cisplatin and metotrexate toxicity, making the above‐mentioned dependencies even more sophisticated (Demiryilmaz et al ., ; Kuduban et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, SOD1 gene has been shown to interact with thiamine biosynthetic regulatory gene THI2 (Zheng et al ., ), showing that the network between thiamine, TDP and defence systems are probably much more complicated than previously presumed. An interesting example of those interactions has been also provided by two different groups, who reported that an oral administration of TDP but not thiamine yielded significant protection against cisplatin and metotrexate toxicity, making the above‐mentioned dependencies even more sophisticated (Demiryilmaz et al ., ; Kuduban et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…than previously presumed. An interesting example of those interactions has been also provided by two different groups, who reported that an oral administration of TDP but not thiamine yielded significant protection against cisplatin and metotrexate toxicity, making the abovementioned dependencies even more sophisticated (Demiryilmaz et al, 2012;Kuduban et al, 2013).…”
Section: Thiamine Alleviates the Damaging Action Of Free Radicals In mentioning
confidence: 99%
“…In recent studies, cisplatin-induced neuropathic pain has been associated with oxidative stress [5]. It has also been documented that cisplatin causes damage to the inner ear tissue with oxidative stress [6]. It has been reported that the oxidative damage caused by cisplatin in the cardiovascular tissue is reduced by an antioxidant drug [7].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from mammalian models lacking hair cell regenerative capacity is equally compelling, both in the context of drug-induced ototoxicity and noise-induced hearing loss. Systemic administration of thiamine pyrophosphate, the active form of the metabolism and antioxidation cofactor thiamine, preserved cochlear antioxidant levels and activities, as well as the presence of hair cells in cisplatin-treated guinea pigs, though hair cell quantification was not part of the analysis (Kuduban et al, 2013). Antioxidant extracts from Ginkgo biloba leaves displayed a dose-dependent attenuation of cisplatin-induced hair cell death and threshold elevations in rat models (Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%